Role of viral and bacterial pathogens in causing pneumonia among Western Australian children: A case-control study protocol - Bhuiyan, M.; Snelling, Thomas; West, R.; Lang, J.; Rahman, T.; Borland, M.; Thornton, R.; Kirkham, L.; Sikazwe, C.; Martin, A.; Richmond, P.; Smith, D.; et al. (BM J Group, 2018)
Introduction: Pneumonia is the leading cause of childhood morbidity and mortality globally. Introduction of the conjugate Haemophilus influenzae B and multivalent pneumococcal vaccines in developed countries including Australia has significantly reduced the overall burden of bacterial pneumonia. With the availability of molecular diagnostics, viruses are frequently detected in children with pneumonia either as primary pathogens or predispose to secondary bacterial infection. Many respiratory pathogens that are known to cause pneumonia are also identified in asymptomatic children, so the true contribution of these pathogens to childhood community-acquired pneumonia (CAP) remains unclear. Since the introduction of pneumococcal vaccines, very few comprehensive studies from developed countries have attempted to determine the bacterial and viral aetiology of pneumonia. We aim to determine the contribution of bacteria and viruses to childhood CAP to inform further development of effective diagnosis, treatment and preventive strategies. Methods and analysis: We are conducting a prospective case-control study (PneumoWA) where cases are children with radiologically confirmed pneumonia admitted to Princess Margaret Hospital for Children (PMH) and controls are healthy children identified from PMH outpatient clinics and from local community immunisation clinics. The case-control ratio is 1:1 with 250 children to be recruited in each arm. Nasopharyngeal swabs are collected from both cases and controls to detect the presence of viruses and bacteria by PCR; pathogen load will be assessed by quantitative PCR. The prevalence of pathogens detected in cases and controls will be compared, the OR of detection and population attributable fraction to CAP for each pathogen will be determined; relationships between pathogen load and disease status and severity will be explored. Ethics and dissemination: This study has been approved by the human research ethics committees of PMH, Perth, Australia (PMH HREC REF 2014117EP). Findings will be disseminated at research conferences and in peer-reviewed journals.